Revisiting Kokkinopilos: Middle Pleistocene radiometric dates for stratified archaeological remains in Greece. (May 2015) - Tourloukis, V.; Karkanas, P.; Wallinga, J.
Abstract: The red-bed site of Kokkinopilos is an emblematic and yet also most enigmatic open-air Palaeolithic site in Greece, stimulating controversy ever since its discovery in 1962. While early research raised claims for stratigraphically in situ artifacts, later scholars considered the material reworked and of low archaeological value, a theory that was soon to be challenged again by the discovery of in situ lithics, including handaxes. Here we present results of a latest and long-term research that includes geoarchaeological assessments, geomorphological mapping and luminescence dating. We show that the site preserves an overall undisturbed sedimentary sequence related to an ephemeral lake, marked by palaeosols and stratigraphic units with Palaeolithic material that is geologically in situ and hence datable. Our study resolves the issues that have been the source of controversy: the depositional environment, stratigraphic integrity, chronological placement and archaeological potential of the site. Moreover, the minimum ages obtained through luminescence dating demonstrate that the lithic component with bifacial specimens considerably pre-dates the last interglacial and therefore comprises the earliest stratigraphically defined and radiometrically-assessed archaeological material in Greece. Kokkinopilos has served as a reference site for the interpretation of all other red-bed sites in north-west Greece, therefore our results have significantly wider implications: by analogy to Kokkinopilos, the open-air sites of Epirus should not anymore be considered 'by default' as inscrutable palimpsests with limited archaeological potential; rather, these sites can be excavated and chronologically constrained. This realization opens up new prospects for future research in Epirus, an area that is the most prolific in Palaeolithic remains in Greece. Highlights: Earliest stratigraphically-defined and radiometrically-assessed archaeological material in Greece. Geoarchaeological and chronostratigraphic assessment of most enigmatic site in Greece. Minimum luminescence (pIRIR) ages point to Middle Pleistocene. Lithic assemblage with bifaces could be (late?) Lower or (early?) Middle Palaeolithic. New prospects for future research at open-air red-bed sites of NW Greece.